2020
DOI: 10.1097/opx.0000000000001558
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Reservoir Thickness and Corneal Edema during Open-eye Scleral Lens Wear

Abstract: SIGNIFICANCE There is debate concerning corneal oxygenation during scleral lens wear due to the potential additive hypoxic effect of a lens plus a fluid reservoir. This study investigated the agreement between theoretical models and empirical measurements of scleral lens–induced corneal edema with respect to central fluid reservoir thickness. PURPOSE The purpose of this study was to examine the effect of altering the fluid reservoir thickness on central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…With ESL assessment, settled PoLTF thicknesses greater than 400 μm were not investigated because Kim et al [22] calculated that thicknesses greater than 400 μm permit buoyancy-driven fluid convection that dominates oxygen mixing compared to molecular diffusion. Therefore, model prediction is accurate up to thicknesses of about 400 μm [22] beyond which a diminishing effect of PoLTF thickness on central corneal edema is expected and in agreement with Fisher et al [48]. Because heat generated by battery-powered embedments may affect buoyancy-driven fluid convection, investigation of PoLTF-temperature profiles is warranted with ESL wear.…”
Section: Dklens = Lencasementsupporting
confidence: 80%
“…With ESL assessment, settled PoLTF thicknesses greater than 400 μm were not investigated because Kim et al [22] calculated that thicknesses greater than 400 μm permit buoyancy-driven fluid convection that dominates oxygen mixing compared to molecular diffusion. Therefore, model prediction is accurate up to thicknesses of about 400 μm [22] beyond which a diminishing effect of PoLTF thickness on central corneal edema is expected and in agreement with Fisher et al [48]. Because heat generated by battery-powered embedments may affect buoyancy-driven fluid convection, investigation of PoLTF-temperature profiles is warranted with ESL wear.…”
Section: Dklens = Lencasementsupporting
confidence: 80%
“…Considering this range, the present study reported an excessive amount of FR thickness in high FR lenses, and although this did not affect HOAs, it might have a negative impact on normal corneal physiology and thus should be avoided. Fisher et al 42 . reported a smaller amount (2%) of corneal oedema after short‐term wear of a SL with a central FR thickness up to 700 microns.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by evidence that corneal neural structures are unchanged with scleral lens wear [366,373]. However, scleral lens materials with an insufficient Dk [374], or with an excessive post-lens tear reservoir [127,128] will produce oedema, suggesting that either scenario may produce a reduced sensitivity.…”
Section: Sensitivity and Nerve Changesmentioning
confidence: 92%
“…Post-lens hypoxia is treated by choosing a lens material with a higher Dk [125,126]. Hypoxia is still an issue for scleral/overnight medical wear due to the effect of the post-lens fluid reservoir [127,128]. • A less stable tear film can be produced in contact lens wear, which induces increased tear evaporation [129][130][131], leading to partial dehydration of the lens material [132,133].…”
Section: Hyperaemiamentioning
confidence: 99%